Efecto del desarrollo del pensamiento crítico sobre la gestión educativa ambiental en los tiempos de COVID-19 - Ramos Guillén, Marta Soledad (2025)
This study examines the relationship between the development of critical thinking and environmental educational management within a secondary-level educational community in Peru, in the context of the COVID-19 pandemic. Employing a mixed-methods approach with a concurrent multilevel design, the research explores how economic, social, and cultural factors influence critical thinking. Through exploratory factor analysis and structural equation modeling, three key dimensions of critical thinking are identified: substantial, contextual, and pragmatic development, with substantial development emerging as the most significant predictor. The findings underscore the importance of pedagogical strategies that enhance both critical and environmental awareness, thereby supporting educational management practices that foster adaptation to emerging environmental and social challenges.